The Quality of Work in the Belgian Service Voucher System - Mousaid, Sarah; Huegaerts, Kelly; Bosmans, Kim; Julià, Mireia; Benach, Joan; Vanroelen, Christophe (International journal of health services, 2017)
Several European countries implemented initiatives to boost the growth of the domestic cleaning sector. Few studies investigated the quality of work in these initiatives, although effects on workers’ health and on social health inequalities can be expected. This study contributes to the scant research on this subject, by investigating the quality of work in the Belgian service voucher system – a subsidized system for domestic work. The applied research methodology includes a qualitative content analysis of parliamentary debates, legislation and previous research about the service voucher system and of 40 in-depth interviews with service voucher workers. The study shows that the legal framework that regulates the system must be further enhanced in order to improve the quality of work in the service voucher system. In addition, the actors involved must be better controlled, and sanctioned in case of non-compliance with legislation.